Syntactic analyses of discourse particles through the microvariation of Basque ote - Monforte, Sergio (Glossa (London), 2020)
In this article I look into dialectal data related to Basque discourse particles and I provide evidence that topics discussed in the literature on discourse particles can also be addressed within Basque microvariation. Four syntactically different types of the particle ote are examined: first, the general pattern found in all dialects where ote functions as a head and occupies a position in the TP-domain; second, the use typical of the eastern dialects where ote behaves as a maximal projection and is located in the CP-domain; furthermore, the configuration formed by wh-words and the discourse particle ote only found in the North-Eastern Basque; and, finally, a novel type of ote only used in the far east of the Eastern Basque (included the Souletin Basque, Amikuze’s variety and also the disappeared variety from the Roncalese valley) which functions as a sentence final particle occurring after all constituents of the clause and, apparently, conveying an intersubjective interpretation, unlike its canonical behaviour. Along with the syntactic data, phonological-prosodic and interpretational evidence also point to the same direction, i.e. to differentiate those four types of ote. This microvariation displayed by the particle ote allows us to compare the different syntactic statuses and positions claimed for discourse particles side by side in the same language; thus, the analysis of their separate properties attains a significant improvement.